2014
DOI: 10.5539/ass.v10n9p171
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Extracurricular Activities on Academic Achievements among the Public University Students in Malaysia

Abstract: The objective of this study is to examine how physical, educational, and social extracurricular activities affect academic achievements of the participating students in Peninsular Malaysia. A cross-sectional design and quantitative method is applied, and complete data is collected from 150 students from three public universities in Peninsular Malaysia. Findings of this study indicate that there is no significant positive association between participation in extracurricular activities and student's academic ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 10 publications
1
13
0
7
Order By: Relevance
“…In addition, participation in extracurricular activities leads to a reduction in dropout rates. 3,12,13 However, a different result was found by Shamsudin et al in Malaysia, whereas they showed that there was not enough evidence to prove a significant positive correlation between extracurricular activities and academic performances. Nevertheless, the government of the country still emphasizing the importance of incorporating extracurricular activities with curricular activities.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, participation in extracurricular activities leads to a reduction in dropout rates. 3,12,13 However, a different result was found by Shamsudin et al in Malaysia, whereas they showed that there was not enough evidence to prove a significant positive correlation between extracurricular activities and academic performances. Nevertheless, the government of the country still emphasizing the importance of incorporating extracurricular activities with curricular activities.…”
Section: Discussionmentioning
confidence: 83%
“…Dunkelberger (1935) argued that curricular activity is not the cause of low academic performance, rather the cause is absenteeism from class due to involvement in curricular activities. A few studies however, found no significant influence of students' participation in curricular activities on their academic performance (Shamsuddin et al, 2014).…”
Section: Curricular Activity and Students' Performancementioning
confidence: 99%
“…Por meio da autonomia e participação ativa, os alunos podem experienciar o autêntico aprendizado com a construção e aplicação dos próprios pensamentos e ideias, o que contribui para a sua motivação com seu percurso acadêmico 14 . A forma de envolvimento dos graduandos nas atividades pode representar resultados diferenciados, participantes com papéis de liderança podem obter melhores desempenhos, senso de realização e autoestima, enquanto aqueles que desempenham envolvimento passivo podem apresentar desfechos mais limitados 15,16 .…”
Section: Autonomia E Desenvolvimento Psicossocialunclassified
“…a melhora no desempenho dos graduandos nas avaliações acadêmicas, considerando a carência de estudos que comprovem tal relação 14,16,21,22 .…”
Section: -124unclassified